Using Si/SiC solid waste to design urchin‐like mullite whiskers for oil‐water separation. Issue 3 (15th January 2022) - Liu, Zhaoyang; Yu, Jingkun; Wang, Xiangnan; Wang, Jiakang; Zhang, Ling; Wen, Tianpeng; Jia, Danbin; Yan, Zhengguo; Yuan, Lei; Ma, Beiyue
Abstract: Using recyclable industrial waste Si/SiC and Al2 (SO4 )3 as starting materials, urchin‐like mullite whiskers were successfully synthesized via the molten salt method. The characterizations were focused on the phase transformations and morphology evolution of mullite whiskers. The circular oxidation‐dissolution‐precipitation mechanism was proposed for the growth of urchin‐like mullite whiskers. Then, the pressing‐sintering process was used for fabricating porous whisker‐structured mullite ceramics for oil‐water separation applications. Physical properties of porous ceramic, including bulk density, apparent porosity, mechanical and thermal shock resistance were measured. It was found that excessive reaction temperature could decompose the mullite, and a suitable temperature for pure urchin‐like mullite whiskers was found to be 900°C. To achieve oil‐water separation, bionic surface grafting technology was used for coating a hydrophobic and lipophilic material (octadecylamine, ODA) on mullite ceramic. Oil adsorption capacities of the ceramic/ODA for various oils, that is, .27 and .24 g/g for cooking and motor oil, respectively, were successfully achieved.